The Effectiveness Of Learning Video Media To Increase Interest In Cognitive Learning Of Kindergarten Children - Rahajeng Ayu Hapsari (Journal of Psychology and Instruction, 2022)
Monotonous learning so that children's interest in learning is low. This study aims to analyze the effectiveness of multimedia-based learning video media (vibel) to increase the cognitive learning interest of Group A children. The type of research is R and D. The development model used in this research is the development model of Borg and Gall with ten development steps. The population in this study was 60 kindergarten children, ten kindergarten teachers, and the head of the kindergarten totaling five people. Data collection techniques used observation, interviews, questionnaires, and documentation. Data analysis techniques include product data analysis, initial data analysis with a normality test, and final data analysis with N-gain and t-tests. The study results are learning video media declared feasible for kindergarten children based on material expert validation of 75 with a decent category and media expert validation of 76 with a decent category. Video media is effectively used to increase the cognitive learning interest of kindergarten children in Rembang. The effectiveness of learning videos based on limited product trials and broad product trials with a t count more than the t table with a t count of 33.53 more than the t table of 2.02 and n gain test in limited tests in the effective category. The implication of this research is expected to stimulate children's cognitive learning interest.